How do patients and health care professionals perceive de-implementation of routine follow-ups after total hip or knee arthroplasty? Protocol for a nested qualitative study within a hybrid effectiveness de-implementation trial - Lex D. de Jong; Dominique C. Baas; Lidy A.C. Roubos; Jantsje H. Pasma; Ariena J. Rasker; Marijn Rutgers; Ronald A.W. Verhagen; Sigrid N.W. Vorrink; Nienke W. Willigenburg; Rudolf W. Poolman (PLoS ONE, 2025)
Background Total hip and knee arthroplasties significantly improve the quality of life for patients with severe osteoarthritis. However, some patients experience complications that require follow-up care. Amid rising demand for these arthroplasties, debates have emerged around the value of routinely scheduled follow-ups (RFUs). This qualitative study, nested within a hybrid effectiveness de-implementation trial that assesses quantitative differences between RFU and check-ups on-demand (COD), will explore and compare the patients’ and health care professionals’ (HCPs) experiences with, and perceptions about, RFU and COD at 1 and 10 years after total hip and knee arthroplasty. Materials and methods First, a pre-study reference panel will be organised to prepare a focus groups topics guide. Subsequently, 2 methods of data collection will be used: 8 focus groups with total of 80 participants from the main trial and 10 in-depth interviews with different HCPs. Thematic analysis using a deductive approach will be performed on anonymised transcripts to identify key themes. For this, the comparative case study framework and the Theoretical Framework of Acceptability will be used. Findings will be used to inform the transition from RFU to COD if deemed acceptable by patients and HCPs.